Academic training in the certification of medical facilities in mexico - Herranz-Sanmartín, Juán Pedro (Horizonte Sanitario, 2015)
The certification of healthcare facilities in Mexico is a established government program, depending of the Presidency of the Republic, as well as global need of the North American Free Trade Agreement (NAFTA) signed by Canada, the US and Mexico, that aligns our country with the progress and development towards a better quality in medical services and with other countries that have developed the accreditation and certification of medical services as a general policy.